Legal Formalism vs Moral Humanism in Contemporary Jurisprudence: A Critical Appraisal - Sapkota, Mahendra (KDCBAR Law Journal, 2025)
In this paper, the author takes a critical look at the conflict between legal formalism and moral humanism in the present-day jurisprudence. Legal formalism is a preference for the meaningful application of the law through hard and fast rules, deductive knowledge, and adherence to moral humanism, which emphasizes ethical and social circumstances, as well as human dignity, in court judgments. The research draws on the classical and modern legal theories of H.L.A. Hart and Ronald Dworkin, as well as those of Martha Nussbaum and Jeremy Waldron, to investigate the role these paradigms play in shaping the interpretation and application of law in formally democratic and pluralistic societies. By providing a qualitative literature review of theoretically oriented and case-based literature, the paper advocates the approach that balances procedural consistency and moral responsiveness as a dimension of jurisprudence. The process of analysis adds to current legal theory literature on the issues of judicial activism and constitutional interpretation, in extending the protection of fundamental rights. The findings of the paper therefore will significantly influence the interpretation and application of law, thereby shaping the legal landscape.